Expanding Access to Social Support in Primary Care via Telemedicine: A Pilot Study - Fipps, David C.; Vickers, Kristin S.; Bergstedt, Beth; Williams, Mark D. (Frontiers in Psychiatry, 2022)
The coronavirus pandemic quickly exposed the need for efficient and widespread implementation of telehealth services. Additionally, it further unveiled the impact of social and environmental barriers to healthcare in underserved, rural populations. This in-practice pilot study tested the utility of a geographically centralized social worker providing services between a patient and a primary care provider via telecommunication at two high volume rural outpatient family practice clinics. Outcome measures included patient and provider satisfaction. Twenty-two telehealth social work encounters occurred spanning both adult and pediatric patients. Data collected from patients, primary care providers, and social work staff revealed positive feedback. The data from our small pilot study demonstrated that social work triage delivered via a tablet was an acceptable and valued resource in busy primary care practices.